Risk of Traumatic Intracranial Hemorrhage In Patients With Head Injury and Preinjury Warfarin or Clopidogrel Use. (13th February 2013) - Nishijima, Daniel K.; Offerman, Steven R.; Ballard, Dustin W.; Vinson, David R.; Chettipally, Uli K.; Rauchwerger, Adina S.; Reed, Mary E.; Holmes, James F.; ,; Zehtabchi, Shahriar
Abstract Objectives Appropriate use of cranial computed tomography (CT) scanning in patients with mild blunt head trauma and preinjury anticoagulant or antiplatelet use is unknown. The objectives of this study were: 1) to identify risk factors for immediate traumatic intracranial hemorrhage (tICH) in patients with mild head trauma and preinjury warfarin or clopidogrel use and 2) to derive a clinical prediction rule to identify patients at low risk for immediate tICH. Methods This was a prospective, observational study at two trauma centers and four community hospitals that enrolled adult emergency department (ED) patients with mild blunt head trauma (initial ED Glasgow Coma Scale [GCS] score 13 to 15) and preinjury warfarin or clopidogrel use. The primary outcome measure was immediate tICH, defined as the presence of ICH or contusion on the initial cranial CT. Risk for immediate tICH was analyzed in 11 independent predictor variables. Clinical prediction rules were derived with both binary recursive partitioning and multivariable logistic regression. Results A total of 982 patients with a mean (± standard deviation [SD]) age of 75.4 (±12.6) years were included in the analysis. Sixty patients (6.1%; 95% confidence interval [CI] = 4.7% to 7.8%) had immediate tICH. History of vomiting (relative risk [RR] = 3.53; 95% CI = 1.80 to 6.94), abnormal mental status (RR = 2.85; 95% CI = 1.65 to 4.92), clopidogrel use (RR = 2.52; 95% CI = 1.55 to 4.10), and headache (RR = 1.81; 95% CI = 1.11 to 2.96) were associated with an increased risk for immediate tICH. Both binary recursive partitioning and multivariable logistic regression were unable to derive a clinical prediction model that identified a subset of patients at low risk for immediate tICH. Conclusions While several risk factors for immediate tICH were identified, the authors were unable to identify a subset of patients with mild head trauma and preinjury warfarin or clopidogrel use who are at low risk for immediate tICH. Thus, the recommendation is for urgent and liberal cranial CT imaging in this patient population, even in the absence of clinical findings.